A non‐local boundary value problem for third‐order linear partial differential equation of composite type - Zikirov, Obidzhan Salidzhanovich (Mathematical Modelling and Analysis, 2009)
In the paper non‐local boundary value problems for a one class of composite type equation with Laplace operator in the main part has been investigated. Using the methods of energy integrals and integral equations, theorems of the uniqueness and existence of a classical solution were proved.First published online: 14 Oct 2010